2016
DOI: 10.1080/10717544.2016.1205158
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal delivery of carboplatin-loaded thermosensitive hydrogel to prevent local cervical cancer recurrence in mice

Abstract: Local tumor recurrence after cervical cancer surgery remains a clinical problem. Vaginal delivery of thermosensitive hydrogel may be suited to reduce tumor relapse rate with more efficacy and safety. A pilot study was carried out to evaluate the efficacy of carboplatin-loaded poloxamer hydrogel to prevent local recurrence of cervical cancer after surgery. In vivo vaginal retention evaluation of 27% poloxamer hydrogel in mice was proven to be a suitable vaginal drug delivery formulation due to its low gelation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…13 In general, HP hydrogel has been widely used for loading and delivering molecules to treat different diseases. 13,14 Recently, Wu et al developed and characterized an HP hydrogel containing acidic fibroblast growth factor (aFGF) for wound treatments and showed a clear therapeutic effect. 15 In addition, HP hydrogel loading nerve growth factor (NGF) enhanced the neuron regeneration in spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In general, HP hydrogel has been widely used for loading and delivering molecules to treat different diseases. 13,14 Recently, Wu et al developed and characterized an HP hydrogel containing acidic fibroblast growth factor (aFGF) for wound treatments and showed a clear therapeutic effect. 15 In addition, HP hydrogel loading nerve growth factor (NGF) enhanced the neuron regeneration in spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…16 We also found that HP hydrogel effectively increased the delivery of NGF via the blood-spinal cord barrier and showed a significant neuroprotective improvement in rats with spinal cord injury. 14 Therefore, a similar delivery system was applied in this study. We provided the first evidence that 17β-estradiol-loaded HP hydrogel effectively enhanced endometrial regeneration and the IUA recovery compared with 17β-estradiol only in cellular and animal models.…”
mentioning
confidence: 99%
“…Hydrogen peroxide trigger-mediated release of drugs could be achieved using hydrogels. This has been demonstrated previously with the use of ABC type triblock copolymer poly [(propylenesulfide)- b -( N , N -dimethylacrylamide)- b -( N -isopropylacrylamide)] [29,30] (PPS- b -PDMA- b -PNIPAM). A model hydrophobic drug, the dye red Nile was encapsulated in the hydrogel in order to demonstrate this.…”
Section: Current Trend In Hydrogel Based Targeted Drug Deliverymentioning
confidence: 65%
“…Its unique properties can be used as a drug carrier, which is injected into the body after being combined with a drug at a low temperature (Le et al, 2018). Forming a colloidal state with the help of body temperature makes it a drug sustained-release system, which simplifies not only medical treatment but also patients' suffering (Wang et al, 2015, 2016; Yang Y. et al, 2016). Main thermosensitive injectable hydrogels include chitosan/glycerophosphate (C/GP), hyaluronic acid (HA), PLGA based hydrogel, PEG-based hydrogel, PECE, and PECT (Guo et al, 2012; Klouda, 2015; Huang et al, 2016; Le et al, 2018; Sapino et al, 2019).…”
Section: Thermosensitive Hydrogelsmentioning
confidence: 99%